Kejelasan Sil'ah sebagai Konsep Objektivikasi Cryptocurrency pada Aplikasi Pintu - zidnaa luthfa hudaaka; iza hanifuddin (Jurnal Ilmiah Ekonomi Islam, 2023)
Abstract The pace of technological development has an impact on the economic world, inevitably triggering the emergence of new breakthroughs in the world of fintech. Crypto, which in several countries began to be recognized as a currency, is now gaining popularity in Indonesia. various polemics emerged, such as the expectation of crypto as a currency by the MUI due to its sil'ah defects. This study aims to interpret the clarity of cryptocurrency sil'ah by relating it to the terms of the contract object. The author tries to dig deeper into how the concept of sil'ah should actually be supported by the theory of the object of the Imam Shafi'i contract. It was found that there were several aspects highlighted, namely the existence, and uncertainty of the number and value of cryptocurrencies so that the gharar aspect arose and the alleged speculation practices behind the defects of this cryptocurrency. Laju perkembangan teknologi berimbas pada dunia ekonomi, tak elak memicu munculnya terobosan baru dalam dunia Fintech. Crypto yang di beberapa negara mulai diakui sebagai mata uang, kini mulai populer di Indonesia. berbagai polemic muncul, seperti pengharaman crypto sebagai mata uang oleh MUI yang disebabkan kecacatan sil‘ahnya. Pengkajian ini bertujuan untuk memaknai kejelasan sil‘ah cryptocurrency dengan mengkaitkannya melalui syarat-syarat objek akad. Penulis berusaha menggali lebih dalam bagaimana sebenarnya konsep sil’ah itu seharusnya didukung dengan teori objek akad Imam Syafi‘i. Didapati hasil bahwa ada beberapa aspek yang disorot, yaitu keberadaan, ketidakpastian jumlah dan nilai cryptocurrency sehingga timbul aspek gharar serta dugaan praktik spekulasi yang melatarbelakangi kecacatan sil’ah cryptocurrency ini.